Business Strategies of Micro Manufacturing Enterprises in the Province of Quezon - Almase, V S (KnE Social Sciences, 2018)
This study examines the business strategies used by the micro manufacturing enterprises in the four districts of Quezon province. More so, it investigated as to what level of extent do these businessmen implemented strategies on production, marketing, human resource management, financial, and research and development. The survey method was used to gather data from 193 Micro Manufacturing Enterprises owners or managers in the entire province of Quezon. They were selected using stratified random sampling method from among the lists provided by the Department of Trade and Industry. More specifically, enterprises analyzed are in the category of Micro with employment capacity ranging from 1-199 employees.Five Null hypotheses were tested to identify the level of extents used by micro manufacturers in terms of production, marketing, human resource management, financial and research and development strategies. Data for this study was analyzed using Statistical Package for Social Sciences (SPSS), and Analysis of Variance (Annova) at.05 level of significance to test the hypotheses. The findings revealed that there are no significant effects on the adoption of strategies pertaining to production, marketing, human resource management, financial and research and development when these respondents were grouped according to age, sex, civil status, and number of trainings participated in. Clearly, the findings of this study disclosed that educational attainment is significantly important when a business has to be sustained and operated at its optimum advantage. Keywords: Business strategies, enterprises, manufacturing, micro